2020
DOI: 10.1007/jhep03(2020)048
|View full text |Cite
|
Sign up to set email alerts
|

BTZ dynamics and chaos

Abstract: We find an effective action for gravitational interactions with scalars in AdS 3 to first order in G N at the conformal boundary. This action can be understood as an action for the Brown-Henneaux modes and is given by the square-root product of right and left moving Schwarzian derivatives for conformal transformations of the boundary. We thus reproduce the result λ L = 2π β for OTOC computed first in arXiv:1412.6087 for a Schwarzchild black hole in AdS 3 . Applying the same procedure to rotating BTZ we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 83 publications
(126 reference statements)
7
71
0
Order By: Relevance
“…For example, in a holographic 2d CFT, one can calculate the OTOC in a rotating ensemble, by repeating the Shenker-Stanford shockwave calculation [11,18,19] for rotating BTZ. This has been done in [20,21], and these authors concluded that the bound λ L ≤ 2π/β is not obeyed. We will re-examine these calculations and will reach a different conclusion.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in a holographic 2d CFT, one can calculate the OTOC in a rotating ensemble, by repeating the Shenker-Stanford shockwave calculation [11,18,19] for rotating BTZ. This has been done in [20,21], and these authors concluded that the bound λ L ≤ 2π/β is not obeyed. We will re-examine these calculations and will reach a different conclusion.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…At strong coupling one has v * = 2/ √ λ 't Hooft [35,36,44], which is small as expected. 20 A cartoon of j(ν) along the imaginary axis is shown on Fig. 11, adapted from [36].…”
Section: Critical Velocity and Exchange Of Dominancementioning
confidence: 99%
See 2 more Smart Citations
“…The resulting 2D theory of gravity contains, in addition to the metric, a gauge field and a dilaton as expected in Kaluza-Klein theory. Our work builds upon the developments in [17,30], where the 2D holographic dictionary was studied by dimensionally reducing the 3D Einstein-Hilbert action with a negative cosmological constant.Other relevant work includes [31], which focuses on the effects of U (1) Chern-Simons fields in 2D; see also [22,[32][33][34][35].One question we investigate is the relation between the nCFT 1 , that describes the near horizon physics of near-extremal BTZ, to the parent CFT 2 , that is dual to AdS 3 . This relation is subtle:The conformal (Weyl) anomaly in AdS 3 /CFT 2 can easily be confused with the anomaly appearing…”
mentioning
confidence: 99%